eNutrilla Education Model Based on Local Food Ingredients Improves Maternal Feeding Behavior and Mothers' Self-Efficacy to Prevent Stunting - Sari, Ignasia Yunita; Indrawati, Nining; Sinaga, Mei Rianita Elfrida; Erawati, Alda Tri; Rumbiak, Christine Ester (Universitas Muhammadiyah Surakarta, 2025)
Stunting poses a significant threat to the future Indonesia. The target of a 14% reduction in stunting has not yet been achieved. However, the 2022 Indonesian Nutrition Status Survey (SSGI) highlights the need for local food ingredients in preparing nutrition for stunting prevention. Utilizing locally available food sources serves as an alternative solution to ensure that children's nutritional needs are met easily and affordably. Education incorporating local wisdom is crucial for stunting prevention. To evaluate the effectiveness of education using the e-Nutrilla model as a method to improve children’s growth status, maternal feeding behavior, and maternal self-efficacy in providing complementary feeding (MPASI). The research design used was a one-group pretest-posttest without control. The population consisted of all mothers with children aged 12–59 months, with a sample size of 36 mothers. The statistical test applied was the Wilcoxon test. All respondents experienced an improvement in maternal feeding behavior categories from pre-test to post-test, with a Mean Rank of 18.50. The mean difference in maternal self-efficacy before and after education was 0.5, with an Asymp Sig. (2-tailed) value of 0.004. Before the intervention, 6 children (16.7%) showed no growth improvement, which decreased to 3 children (8.3%) after the intervention, with an Asymp Sig. (2-tailed) value of 0.257. The e-Nutrilla education model has a positive effect on maternal feeding behavior and maternal self-efficacy but does not significantly impact children’s growth status.